Expert studies of violations of the operating conditions of automobile engines when using them in aviation - Khrulev, Alexander; Saraievа, Iryna; Хрулєв, Олександр Едуардович; Сараєва, Ірина Юріївна (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The features of the design and operation of piston engines in general aviation are considered. Comparative analysis of design features and parameters of automobile and aircraft engines is carried out. It is shown that car engines, despite the high technical level achieved at the beginning of the 21st century, do not technically meet aviation requirements. At the same time, engines created on the basis of automobiles through their deep modernization meet aviation requirements, however, modernization and adaptation of a standard automobile engine to aviation use in terms of costs compared to the creation of a new engine. Purpose. Carry out research on the failure of automobile engines used in light aviation. Methodology. Rough calculations of the service life of an automobile engine were made based on standard driving tests and a flight plan. According to the results of calculations, it has been established that the resource of a standard automobile engine in aviation is reduced many times due to prolonged operation at high loads and rotational speed that are not characteristic of ordinary automotive applications. Results. Experimental data have been obtained on the actual failure of standard automobile engines in aviation during the operating time, significantly less resource of aircraft engines of well-known brands. Based on the results of the study, it was concluded that the use of general aviation automobile engines is economically ineffective due to a short resource and insufficient reliability. Originality. Modern automobile engines, despite their technical perfection, cannot be used in aviation, since they do not correspond to aviation operating conditions. At the same time, adaptation of automobile engines to aviation applications is possible, but requires significant design changes, which makes their single use, as a rule, technically impractical and economically ineffective. Practical value. Due to the fact that saving on an aircraft engine is unacceptable from the point of view of flight safety, the aviation use of automobile engines without special modernization carries excessive risks of failures and their consequences. As a result, serial aircraft engines Lycoming, Continental, Jabiru, ULPower, Rotax, Limbach and others have virtually no alternative in general aviation
Експертні дослідження порушень умовексплуатації автомобільних двигунів при використанні їх в авіації
Keywords: transport; engine; diagnostics; malfunction; failure; driving cycle; expertise; транспорт; двигун; діагностика; несправність; відмова; їздовий цикл; експертиза; 629.083.621; 10.30977/VEIT.2021.19.0.53